The ruptures of American capital : women of color feminism and the culture of immigrant labor - Hong, Grace Kyungwon (University of Minnesota Press, 2006)
The Ruptures of American Capital examines women of color feminism and racialized immigrant women's culture in order to argue that race and gender are contradictions within the history of U.S. capital that should be understood as marked by its crises. Interweaving discussion of U.S. political economy with literary analyses, Grace Kyungwon Hong challenges the fetishization of difference that is one of the markers of globalization.